Pendidikan Karakter pada Psikolinguistik Bahasa Arab - Rusydi, Muhammad (Al-Ulum, 2013)
This article is going to discuss about psycholinguistics point of view in the Arabic language which is oriented to character education. When education meets some principles obstacle in putting human be a human to be better as basic orientation of education, national character education emerges with four pillar of development whichare included heart cultivation, thought cultivation, sense cultivation, and physical cultivation as the manifestation of Pancasila moral values. In psycholinguistic point of view, Arabic language lesson tends to be considered as an activity which erodes nationalism in using Indonesia language as united language. However, Arabic language can be a process to strengthen the nationalism by integrating the four pillar of national character education in learning Arabic language.